Pemikiran Pendidikan Islam Syekh Ahmad al-Qushashi dan Relevansinya di Era Modern - Fathoni, Hanif (Tebuireng: Journal of Islamic Studies and Society, 2022)
Islamic education of Indonesia cannot be separated from the role of previous middle eastern scholars. Sheikh Ahmad al-QushÄshÄ« is one of the middle eastern scholars who influenced previously the thinking of Indonesian scholars, whose students took many roles in Indonesian history. Some of the problems discussed in this study are the objectives, methods, educational curriculum and patterns of teacher-student interaction according to Sheikh Ahmad al-QushÄshÄ« and their relevance to modern education in Indonesia. This research is a library research with analytical descriptive method, with several literature sources examined such as as-Simth al-Majid, ManÅ¼Å«mah al-TawhÄ«d, and other sources. The data analysis technique used is content analysis initiated by Shelley and Krippendorff. The results of research on the educational thinking of al-QushÄsh are briefly as follows: the purpose of education according to al-QushÄsh is to unite God, and become a pious servant. The educational curriculum is a curriculum based on monotheism which is divided into common, special and very special. The al-QushÄshÄ« curriculum approach has an integration pattern between exoteric and esoteric sciences. The method of al-QushÄshÄ« education is the exemplary method, bai'at-talqÄ«n, al-Åœuhbah and al-ta'dÄ«b, taslÄ«m, and IlbÄs. The pattern of teacher-student interaction has a familial pattern of interaction (teachers act as parents, educators, and student guides), so that his thoughts are quite relevant to the modern era.